Applying True or False Method to Improve Learning on Faith in Elementary Students - Saputra, Hijrah; Fikri, Miftahul (Jurnal Keprofesian Guru Keagamaan, 2024)
The success of learning is greatly influenced by a teacher's ability to design effective teaching strategies. Low student enthusiasm has a negative impact on learning outcomes, highlighting the need for improvement. One proposed approach is the True or False learning model, which can enhance student engagement. This study aims to improve students' learning outcomes on the topic of faith in qadha and qadar in class VI at MIN 2 Aceh Timur through the application of this model. The method used is action research with two cycles, each consisting of four stages: planning, action and observation, reflection, and revision. The target of the research is class VI students, with data collected from formative tests and observation sheets. The analysis results indicate a significant improvement in student learning outcomes. The mastery level in cycle I reached 74.10%, increasing to 85.19% in cycle II. The average student score also rose from 75 in cycle I to 82.8 in cycle II. Additionally, student activity increased from 66.67% in cycle I to 96.3% in cycle II. Therefore, the True or False model is effective in enhancing students' learning outcomes and engagement in Akidah Akhlak lessons.